TREE VOLUME AND CARBON STOCKS OF YANGNA (DIPTEROCAPUS ALATUS ROXB EX G.DON.) IN DONCHAOPU FOREST OF LAOVEING COMMUNITY, KALASIN PROVINCE - Chantamontri , Winyu; Cheamsathit , Chuthamat; Chaitieng, Tunwa (Life Sciences and Environment Journal, 2023)
The objective of this research was to investigate the tree volume, biomass, and carbon sequestration of Yangna (Dipterocapus alatus Roxb. ex G.don.) in 52 rai of Donchoapu forest of Ban Klang Muen Community, Kalasin Province. A survey was conducted to find Yangna, which has a circumference greater than or equal to 14.14 centimeters and a height greater than or equal to 1.30 meters. Tree height and Girth at Breast Height (GBH) were measured. The biomass was analyzed by applying an allometric equation. The results showed that there were 211 trees. The highest of GBH was 6.73 meters, the lowest was 0.34 meters and the average (GBH) was 1.99 meters. The highest height of the tree was 57 meters, the lowest height of the tree was 5.00 meters, and the average height of the tree was 31.07 meters. In addition, our findings revealed that the total tree volume was 79.67 /m3 and the biomass of Yangna in this forest community was 36.84 tons/rai. The carbon sequestration was 17.31 tons carbon/rai and 63.54 tons carbon dioxide/rai.